Stenotrophomonas maltophilia as an Emerging Ubiquitous Pathogen: Looking Beyond Contemporary Antibiotic Therapy - Adegoke, Anthony A.; Stenström, Thor A.; Okoh, Anthony I. (Frontiers in Microbiology, 2017)
Stenotrophomonas maltophilia is a commensal and an emerging pathogen earlier noted in broad-spectrum life threatening infections among the vulnerable, but more recently as a pathogen in immunocompetent individuals. The bacteria are consistently being implicated in necrotizing otitis, cutaneous infections including soft tissue infection and keratitis, endocarditis, meningitis, acute respiratory tract infection (RTI), bacteraemia (with/without haematological malignancies), tropical pyomyositis, cystic fibrosis, septic arthritis, among others. S. maltophilia is also an environmental bacteria occurring in water, rhizospheres, as part of the animals’ microflora, in foods, and several microbiota. This review highlights clinical reports on S. maltophilia both as an opportunistic and as true pathogen. Also, biofilm formation as well as quorum sensing, extracellular enzymes, flagella, pili/fimbriae, small colony variant, other virulence or virulence-associated factors, the antibiotic resistance factors and their implications are considered. Low outer membrane permeability, natural MDR efflux systems and/or resistance genes, resistance mechanisms like the production of two inducible chromosomally encoded β-lactamases, and lack of carefully compiled patient history are factors that pose great challenges to the S. maltophilia control arsenals. Also, the fluoroquinolone, some tetracycline derivatives and trimethoprim-sulphamethaxole (TMP-SMX) were reported as effective antibiotics with good therapeutic outcome. However, TMP-SMX resistance and allergies to sulfa as well high toxicity of fluoroquinolone are notable setbacks. S. maltophilia’s production and sustenance of biofilm by quorum sensing enhance their virulence, resistance to antibiotics and gene transfer, making quorum quenching imperative step in Stenotrophomonas control. Incorporating several other proven approaches like bioengineered bacteriophage therapy, Epigallocatechin-3-gallate (EGCG), essential oil, nanoemulsions, and use of cationic compounds are recommended to be incorporated in Stenotrophomonas control arsenal.